2023
DOI: 10.1001/jamanetworkopen.2023.0736
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Safety Outcomes of Carotid Artery Stenting and Mechanical Thrombectomy for Large Vessel Occlusion Ischemic Stroke With Tandem Lesions

Abstract: ImportanceApproximately 10% to 20% of large vessel occlusion (LVO) strokes involve tandem lesions (TLs), defined as concomitant intracranial LVO and stenosis or occlusion of the cervical internal carotid artery. Mechanical thrombectomy (MT) may benefit patients with TLs; however, optimal management and procedural strategy of the cervical lesion remain unclear.ObjectiveTo evaluate the association of carotid artery stenting (CAS) vs no stenting and medical management with functional and safety outcomes among pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…We previously found that acute CAS for cervical lesions during EVT of TLs was associated with improved functional outcomes and reperfusion rates compared with nonstenting. 3,9 In this subanalysis of a multicenter TL registry, we demonstrate for the first time to our knowledge, that up to 25% of the total treatment effect of acute CAS on the functional outcome in patients with TL undergoing EVT could be explained by its positive additional effect on reperfusion status. Our results also suggest that additional unrecognized characteristics and mechanisms account for the remaining 75% of the treatment effect.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We previously found that acute CAS for cervical lesions during EVT of TLs was associated with improved functional outcomes and reperfusion rates compared with nonstenting. 3,9 In this subanalysis of a multicenter TL registry, we demonstrate for the first time to our knowledge, that up to 25% of the total treatment effect of acute CAS on the functional outcome in patients with TL undergoing EVT could be explained by its positive additional effect on reperfusion status. Our results also suggest that additional unrecognized characteristics and mechanisms account for the remaining 75% of the treatment effect.…”
Section: Discussionmentioning
confidence: 72%
“…4 More recently, our group found that patients treated with acute CAS had better mRS scores of 0–2 at 90 days compared with patients treated with acute balloon angioplasty alone or those whose ICA treatment was deferred by 24 hours or more (54.5% vs 36.7%; adjusted OR 1.67). 3 Finally, ongoing trials such as TITAN and EASI-TOC will provide further insights into whether acute CAS offers superior safety and efficacy compared with a non-CAS approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Clinically relevant variables were used for adjustment for the outcome measures. 5,23 Multiple Imputation by Chained Equations was used for handling the missing observations, and only variables missing <20% data were included. 24 Quality of imputation was assessed graphically through density plots for imputed observations.…”
Section: Discussionmentioning
confidence: 99%
“…Patient eligibility and methods of collaboration have been reported previously. 24 Briefly, the study included adult patients with TL treated with MT within 24 hours after stroke onset from 16 stroke centers (15 hospitals in the United States and 1 in Spain) between January 2015 and December 2020. TL was defined as an intracranial LVO (petrous, sigmoid, or terminus segment of the internal carotid artery (ICA) or M1 or proximal M2 segment of the middle cerebral artery) with concomitant extracranial ICA stenosis ≥70% according to NASCET (North American Symptomatic Carotid Endarterectomy Trial).…”
Section: Study Populationmentioning
confidence: 99%